2019
DOI: 10.2147/clep.s222726
|View full text |Cite
|
Sign up to set email alerts
|

<p>Do Gestational Obesity and Gestational Diabetes Have an Independent Effect on Neonatal Adiposity? Results of Mediation Analysis from a Cohort Study in South India</p>

Abstract: Purpose: Neonates born to mothers with obesity or gestational diabetes mellitus (GDM) have an increased chance of various metabolic disorders later in life. In India, it is unclear whether maternal obesity or GDM is related to offspring adiposity. We aimed to understand the independent effect of maternal obesity and GDM with neonatal adiposity and whether GDM has a mediating effect between maternal obesity and neonatal adiposity. Methods: We recruited a cohort of 1120 women (between April 2016 and February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…However, most likely due to the discrepancies in race and the condition of GDM and overweight/obesity among woman of childbearing age between countries, the highest mediated proportion (up to 16%) observed by Kondracki et al [ 17 ] was relatively lower than that observed in this study. Babu and colleagues [ 35 ] recruited a cohort of 1120 women of all BMI ranges from Bangalore, India, and revealed a mediator effect of GDM between maternal obesity and neonatal adiposity. Given the generalized increase in body fat of the macrosomic fetuses [ 36 ], the observations of Babu and colleagues also provided evidence for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, most likely due to the discrepancies in race and the condition of GDM and overweight/obesity among woman of childbearing age between countries, the highest mediated proportion (up to 16%) observed by Kondracki et al [ 17 ] was relatively lower than that observed in this study. Babu and colleagues [ 35 ] recruited a cohort of 1120 women of all BMI ranges from Bangalore, India, and revealed a mediator effect of GDM between maternal obesity and neonatal adiposity. Given the generalized increase in body fat of the macrosomic fetuses [ 36 ], the observations of Babu and colleagues also provided evidence for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In India, measuring MUAC in pregnancy and birth weight to assess obesity can help plan and prevent potential adverse outcomes. We recently showed that maternal obesity is an independent risk factor for neonatal adiposity [ 44 ]. Total skinfold measurement, the preferred method for assessing obesity, is often impeded by the dearth of trained staff, time, and costly equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The participating hospital had an obstetric department that caters to the urban population of Bengaluru in the surrounding vicinity. A detailed protocol and related publications can be found elsewhere [17,31].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Advanced maternal age, high body mass index (BMI), a family history of T2DM are significant independent risk factors for hyperglycemia in pregnancy [14]. Among other modifiable risk factors of GDM, tackling obesity is essential; even moderate changes in pre-pregnancy weight have shown to affect the risk of gestational diabetes among obese women [5,[15][16][17]. Studies have also shown that minor degrees of carbohydrate intolerance are related to obesity [18].…”
mentioning
confidence: 99%